Extrinsic incubation temperature impacts on Zika virus evolution and vector competence during systemic Aedes infection - Murrieta, Reyes David A., author; Ebel, Gregory, advisor; Olson, Kenneth, committee member; Stenglein, Mark, committee member; Sloan, Dan, committee member (Colorado State University. Libraries, 2020)
Arthropod-borne viruses (arboviruses) are distinctive in that they are required to constantly replicate in different hosts and in a wide range of temperatures for their perpetuation in nature. Vertebrate hosts tend to maintain temperatures of approximately 37°C - 40°C, but arthropods hosts are poikilotherms and subject to ambient temperatures which can have a daily temperature fluctuation of > 10°C. Invertebrate host genus, species, and strain in combination with arbovirus strain and preparation methods are known to have large impacts on vector competence and vectorial capacity. Seemingly small differences in host geographic isolation, virus strain, and preparation methods can have significant impacts on vector competence studies. The role of temperature on the ability of an arthropod vector to acquire, maintain, and transmit a pathogen has been investigated for numerous arboviruses. Changing the extrinsic incubation temperature between distinct constant temperatures has been shown to alter arbovirus vector competence, extrinsic incubation period, and mosquito survival, in which moderate temperatures of 28°C-32°C are optimal and temperatures higher and lower have deleterious effects. The mean and range of daily temperature fluctuations (diurnal temperature) have likewise been shown to influence arbovirus perpetuation and vector competence, in which large daily temperature fluctuations negatively affect mosquito development, survival, and vector competence. However, little is known as to how temperature alters arbovirus genetic diversity during systemic mosquito infection or how differences in arbovirus hosts and viral strains impact arbovirus genetic diversity in relationship to temperature. Therefore in the study completed in chapter two, we characterized the impact that constant temperatures of 25°C, 28°C, 32°C, and 35°C, and the diurnal fluctuation from 25°C to 35°C during extrinsic incubation periods have on the Puerto Rican isolate of Zika virus (ZIKV) vector competence and population dynamics within Aedes aegypti (Poza Rica) and Aedes albopictus (Florida) mosquitoes. To characterize the impact that temperature has on ZIKV population diversity in different host species and viral isolates, in the study completed in chapter three, we used a Tapachula, Mexico Aedes aegypti line and a Chiapas, Mexico ZIKV isolate to assess ZIKV population dynamics during 20°C, 24°C, 28°C, 32°C, 34°C, and 36°C constant extrinsic incubation temperatures. We found that vector competence varied in a unimodal manner for constant temperatures peaking between 28°C and 32°C for both Aedes species, while transmission peaked at 10 days post-infection for Aedes aegypti and 14 days post-infection in Aedes albopictus. The diurnal temperature group is not predicted by the constant temperature distribution. Instead, when using the mean daily temperature of the diurnal group as a predicter, its VC lies between the moderate (28°C and 32°C) and extreme (25°C and 35°C) temperature group VCs. Using RNA-seq to characterize ZIKV population structure, we identified that temperature alters the ZIKV selective environment during infection. During mosquito infection, constant temperatures more often elicited positive selection whereas diurnal temperatures led to strong purifying selection in both Aedes species. These findings demonstrate that temperature has multiple impacts on ZIKV biology within mosquitoes and has distinct effects on the selective environment within mosquitoes. Additionally, the selective pressures induced by temperature are consistent across host species and viral strain and have similar impacts on shaping the viral population structure. However, input viral populations are still a driving factor of diversity and expansion during systemic mosquito infection. While our findings and those of others suggest that vector competence is impacted unimodally regardless of temperature, this is only applicable for constant temperatures. Future work assessing daily temperature fluctuation range and mean are needed to have a clear understanding of the role extrinsic incubation temperature plays on vector competence.
Keywords: flavivirus; selection; population diversity; arbovirus; vector competence; Zika virus